Big Data Analytics in the Public Sector: A Systematic Literature Review - Muhammad Choirul Huda; Bambang Jatmiko (Journal of Accounting and Investment, 2025)
Research aims: This study investigates previous research on big data analytics. This study aims to evaluate journals that discuss big data in the public sector to find lessons that may be useful for dealing with similar situations in the future and with more complex topics. Design/Methodology/Approach: This study used a review procedure following Hoque (2014) with modifications, including keyword analysis to map themes. Journals to be reviewed were identified by entering the search keywords “Big” AND “Data” and “Sector” AND “Public” in the Scopus database. After applying a set of criteria, 64 journals were used in the subsequent analysis. The background of the journal year, theory, country and findings, and lessons learned are discussed. Research findings: This research resulted in six research themes based on the analyzed literature: (1) Accountability - emphasizing responsibility and transparency in decision-making; (2) Energy Efficiency - a system or process is able to produce the desired output using less energy; (3) Sustainability - can be used to support the development of sustainable policies; (4) Innovation - creating new services or improving existing ones; (5) Big Data Analytics - being an invaluable tool to improve efficiency, responsiveness, and quality of services; (6) Governance - covering how governments manage, secure, and use big data to achieve public service goals. Theoretical contribution/ Originality: To the best of the author's knowledge, there has been no literature review research on Big Data in the Public Sector, so researchers feel the need to conduct this research. Given also the importance of understanding Big Data analysis in the Public Sector. Furthermore, this research also explains what lessons can be learned by other parties or future research. Practitioner/Policy implication: This study can be used by business leaders in companies or public sector organizations to make smarter and more informed policies, identify social trends, and measure policy impact more accurately through big data analytics. This research can also be used to evaluate the value relevance of certain government policies in the public sector regarding big data analytics. Research limitation/Implication: Future research is expected to further study and research: (1) The Impact of Big Data on the Public Sector using journals or other references outside the Scopus database; (2) Future research can use keywords that are different from this research, (3) and can also access more journals to be reviewed. Keywords: Big Data, Public Sector, Literature Review